Lighting for photographers :an introductory guide to professional photography - Lavine, Joe (Routledge, 2020)
Lighting is one of the most important aspects of any photograph. The best images create dimension and drama, which goes beyond formulas and lighting recipes. In Lighting for Photographers: An Introductory Guide to Professional Photography, commercial photographers and instructors Joe Lavine and Brad Bartholomew offer a unique philosophy of lighting, starting with an understanding of the characteristics of lighting to build great shots.